2018
DOI: 10.1111/afe.12299
|View full text |Cite
|
Sign up to set email alerts
|

Tight insect–host phenological synchrony constrains the life‐history strategy of European pine sawfly

Abstract: 1 The synchronization of insect and plant phenologies may impose ecological constraints on host specialization and the evolution of life histories. 2 European pine sawfly Neodiprion sertifer (Geoffroy) feeds on mature foliage of Scots pine Pinus sylvestris L. during a limited temporal period in early spring and is univoltine despite the continual presence of this resource throughout the growing season. Reciprocal manipulation of host and insect phenologies demonstrated that larval performance was highest in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
(80 reference statements)
0
2
0
1
Order By: Relevance
“…Synchronization of the phenology between insect development and plant growth is critical for establishing populations of range‐expanding insect herbivores (Chorbadjian et al, 2019; Posledovich et al, 2018). We found that the larval stage of the wood‐borer matched with the growing season of the woody plant, thereby indicating that the range‐expanding insect herbivore could potentially be adapted to the developmental phenology of its new host plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchronization of the phenology between insect development and plant growth is critical for establishing populations of range‐expanding insect herbivores (Chorbadjian et al, 2019; Posledovich et al, 2018). We found that the larval stage of the wood‐borer matched with the growing season of the woody plant, thereby indicating that the range‐expanding insect herbivore could potentially be adapted to the developmental phenology of its new host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronization of the phenology between insect development and plant growth is critical for establishing populations of range-expanding insect herbivores (Chorbadjian et al, 2019;Posledovich et al, 2018).…”
Section: Phenological Synchronization Drives Sapling Damagementioning
confidence: 99%
“…Це створило умови для успішного розвитку двох поколінь і значного збільшення чисельності популяцій наприкінці вегетаційного періоду, коли пошкодження личинками хвої поточного року є найнебезпечнішим для дерев сосни. Це узгоджується з даними стосовно залежності динаміки популяцій комаххвоєгризів від погодних умов у різних регіонах Möller et al, 2017;Haynes et al, 2014Haynes et al, , 2018Chorbadjian et al, 2019).…”
Section: таблunclassified